2016
DOI: 10.3944/aott.2016.15.0144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the lower extremity external fixators on the sexual life of males

Abstract: EF in the cruris may impair sexual functions in males. The rate of SD was higher in male patients who were treated with EF. Thus, SD might be associated with physical, psychological, and social limitations caused by EF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…After one-year recovery, 60% of the patients could do sexual activity more easily than the previous year, 84% of these patients suffered from less pain, and 30% experienced greater mobility or range of motion. In the study of Adas et al,[ 15 ] postoperative sexual functions were found to be similar to preoperative sexual functions in 12 (11%) of 108 patients who underwent external fixation. However, postoperative scores decreased in 96 (89%) patients.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…After one-year recovery, 60% of the patients could do sexual activity more easily than the previous year, 84% of these patients suffered from less pain, and 30% experienced greater mobility or range of motion. In the study of Adas et al,[ 15 ] postoperative sexual functions were found to be similar to preoperative sexual functions in 12 (11%) of 108 patients who underwent external fixation. However, postoperative scores decreased in 96 (89%) patients.…”
Section: Discussionmentioning
confidence: 82%
“…None of the patients reported permanent sexual dysfunction. [ 15 ] In the study of Shulman et al,[ 10 ] among patients who had orthopedic trauma that did not include the pelvic region, sexual dysfunction was reported in 31% of proximal humerus fracture patients, 32% of distal radius fracture patients, 47% of tibial plateau patients, 11% of ankle fracture patients, and 42% of long bone nonunion at three-month follow-up. In the study by Nugent et al,[ 12 ] 65% of patients with rotator cuff tears reported that their shoulders interfered with the quality and/or frequency of their sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Since the definition and diagnostic criteria for SD are still controversial and under development, estimating the prevalence of SD is relatively difficult. However, SD has been reported in 10–52% of men and 25–63% of women worldwide [ 13 , 14 ]. Even in sexually active young patients, post-traumatic SDs are often overlooked, leading to depression and a decrease in QoL [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…While changes in sexual life after EF treatment in men have been investigated, the effects in women are unknown [ 14 ]. Therefore, this retrospective study aimed to compare sexual dysfunction associated with external and internal fixation of traumatic diaphyseal tibial fracture in women using the 19-item Female Sexual Function Index (FSFI).…”
Section: Introductionmentioning
confidence: 99%